DETERMINAN KUALITAS LAPORAN KEUANGAN PADA OPD KABUPATEN LANDAK - Febriansyah, Erwin; Muliawati, Muliawati; Nasution, Hilfa Mora Marito; Dhayan, Hana (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2025)
This research was conducted to analyze the influence of the use of information technology, the quality of human resources and work experience on the quality of financial. The theories used in this research are agency theory and decision-use theory. This type of research is quantitative research. The sample used in this research was state civil servants (ASN) who were involved in the process of preparing financial reports for regional apparatus organizations (OPD) in Landak Regency. Hypothesis testing uses an analysis method with a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) with WarpPLS 8.0 software. The results of this research show that the use of information technology, quality of human resources, and work experience has a significant effect on the quality of reports with a positive effect on the use of information technology and the quality of human resources, work experience has a negative effect on the quality of financial reports.